2022
DOI: 10.3389/fonc.2022.900478
|View full text |Cite
|
Sign up to set email alerts
|

CT-Based Radiomics Analysis for Noninvasive Prediction of Perineural Invasion of Perihilar Cholangiocarcinoma

Abstract: PurposeThe study aimed to construct and evaluate a CT-Based radiomics model for noninvasive detecting perineural invasion (PNI) of perihilar cholangiocarcinoma (pCCA) preoperatively.Materials and MethodsFrom February 2012 to October 2021, a total of 161 patients with pCCA who underwent resection were retrospectively enrolled in this study. Patients were allocated into the training cohort and the validation cohort according to the diagnostic time. Venous phase images of contrast-enhanced CT were used for radiom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…The key lies in the accurate preoperative prediction of potential PNI occurrence. Advances have been made, such as the development of radiomic-based predictive models that forecast the PNI status in cholangiocarcinoma non-invasively, enabling more tailored surgical planning and precise targeted and immunotherapy regimens ( 128 , 129 ). Yet, when considering therapies targeting neural pathways, potential side effects cannot be overlooked, given the autonomic nervous system’s critical role in digestive functions.…”
Section: Discussionmentioning
confidence: 99%
“…The key lies in the accurate preoperative prediction of potential PNI occurrence. Advances have been made, such as the development of radiomic-based predictive models that forecast the PNI status in cholangiocarcinoma non-invasively, enabling more tailored surgical planning and precise targeted and immunotherapy regimens ( 128 , 129 ). Yet, when considering therapies targeting neural pathways, potential side effects cannot be overlooked, given the autonomic nervous system’s critical role in digestive functions.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the fusion radiomics signature performed better predictive capability to evaluate prognosis [ 35 ]. Zhang and Zhan et al also constructed radiomics model for the preoperative prediction of PNI in patients with prostate cancer and perihilar cholangiocarcinoma, respectively [ 36 , 37 ]. However, no predictive nomogram was constructed to predict the PNI probability of PHAC patients, and single CA19-9 or blood glucose level reflected the PNI probability was limited, thus, it needs to development a novel predictive model to assess the PNI probability accurately in PHAC patients.…”
Section: Discussionmentioning
confidence: 99%
“…The predictive value of radiomics-based techniques for PNI has been widely studied in various types of cancer (12)(13)(14)(15). However, radiomic studies focusing on PNI in GC are limited, and the sample sizes are relatively small (16).…”
Section: Introductionmentioning
confidence: 99%